Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1037/a0018097
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for skepticism about the efficacy of simulated social contact interventions.

Abstract: Crisp and Turner (May-June 2009) argued that imagining intergroup interactions reduces intergroup prejudice. They argued that the procedure is remarkably effective, with "significant potential application for policymakers and educators seeking to promote tolerance for social diversity" (p. 238). We believe that such interventions, although appealing to many individuals, are problematic and that the authors' conclusions are overly optimistic. We believe that simulated contact interventions are highly unlikely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 8 publications
1
34
1
Order By: Relevance
“…Thus, in line with previous studies, imagined contact proved to be an effective strategy to improve intergroup relations among children from 8 to 10 years of age. Moreover, the present findings help overcome some of the reasons for skepticism on imagined contact posed by Bigler and Hughes (2010). For instance, Study 1 demonstrated that imagined contact can be used in multiple-session interventions and that interventions based on imagined contact can have long-lasting effects of at least two weeks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, in line with previous studies, imagined contact proved to be an effective strategy to improve intergroup relations among children from 8 to 10 years of age. Moreover, the present findings help overcome some of the reasons for skepticism on imagined contact posed by Bigler and Hughes (2010). For instance, Study 1 demonstrated that imagined contact can be used in multiple-session interventions and that interventions based on imagined contact can have long-lasting effects of at least two weeks.…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, in Study 1, a field intervention with children, we will assess dependent variables one week and two weeks after the end of the intervention. Assessing the longevity of effects is important in order to show that imagined contact can produce meaningful attitude change, thus contributing to the increasing canon of research supporting imagined contact effects, and directly addressing initial skepticism expressed about the utility of this strategy (Bigler & Hughes, 2010). …”
mentioning
confidence: 99%
“…Since its inception [38], the imagined contact hypothesis has met with skepticism including claims that it cannot be implemented in conflictual intergroup settings and that it is a result of demand characteristics [39,40]. Yet it has continued to receive empirical support.…”
Section: Imagined Contactmentioning
confidence: 99%
“…Most research has examined the effects immediately after the imagined contact intervention and, as noted, these effects are relatively small [41**], raising the question as to whether the improvements are just short-term reactions to the experimental materials rather than substantive changes to intergroup bias [39]. However, longitudinal effects of imagined contact have been observed with both school and university students [28, [43][44][45].…”
Section: Imagined Contactmentioning
confidence: 99%
See 1 more Smart Citation